The Role of Phosphate Functionalization on the Oxygen Evolution Reaction Activity of Cobalt‐Based Oxides at Different pH Values - Wataru Yoshimune; Juliana B. Falqueto; Adam H. Clark; Nur Sena Yüzbasi; Thomas Graule; Dominika Baster; Mario El Kazzi; Thomas J. Schmidt; Emiliana Fabbri (Small Structures, 2023)
Cobalt‐based oxides have attracted attention as active electrocatalysts for the oxygen evolution reaction (OER) in alkaline electrolytes. However, highly OER active catalysts at near‐neutral pHs are also desired for practical applications. Herein, a dry phosphate functionalization process is presented to enhance the OER activity of different cobalt‐based catalysts at near‐neutral pHs. Electrochemical evaluations show that the P‐functionalization can effectively improve the OER activity at near‐neutral pHs for La0.2Sr0.8CoO3–δ , La0.2Sr0.8Co0.8Fe0.2O3–δ , and CoO x catalysts, but not for La0.5Sr1.5CoO4–δ . Bulk and surface sensitive X‐ray absorption spectroscopy and X‐ray photoelectron spectroscopy unveil the influence of P incorporated in the order of ppm on the electronic state, local structure, and surface composition of the investigated catalysts. The P‐functionalization reduces the Co oxidation state in La0.2Sr0.8CoO3–δ and La0.5Sr1.5CoO4–δ , but the latter also presents significant Sr‐based segregations on the surface‐inhibiting OER activity at near‐neutral pHs. Differently, La0.2Sr0.8CoO3–δ , and to a lesser extent La0.2Sr0.8Co0.8Fe0.2O3–δ and CoO x , shows improved OER activity at neutral pH after the P‐functionalization. The findings disclose that P‐functionalization successfully enhances OER activity at near‐neutral pHs and that both phosphate ion assistance in the OER mechanism and catalyst Co oxidation state can play a role in the enhanced OER activity.